EVALUATION OF BADAN USAHA MILIK DESA AS A LOCOMOTIVE FOR VILLAGE DEVELOPMENT IN YOGYAKARTA SPECIAL REGION - Sugiyanto, Sugiyanto; Wahyuni, Raden Roro Elisabeth Anggraeni Eksi (Universitas Negeri Yogyakarta, 2021)
Village-Owned Enterprises or Badan Usaha Milik Desa (BUM Desa) is institution that promote economic growth that have a role related to the hope of bringing changes in the welfare of rural communities for the better. The purpose of this research is to know the characteristics of BUMDesa in the study location and evaluate the existence of these institutions. This study uses a qualitative method with a case study approach. The results showed that the characteristics of BUM Desa were formed at the initiation of the village government and were welcomed by the community. Natural potential is the main capital in developing BUM Desa. The main problem of BUM Desa is the quality of human resources and capital in developing business units. In terms of institutional success indicators, the business unit is able to have a positive impact on the community and village government. In terms of internal support and other institutions, BUM Desa institutions have collaborated with various institutions both local and international scales. In terms of leadership, the character of a leader who is visionary, professional, political, multitalent, and able to mingle with members so that he becomes a role model for members.